Does the COVID-19 XBB Omicron subvariant signal the beginning of the end of the pandemic? - Jinghao Nicholas Ngiam; Abdurrahmaan Al-Mubaarak; Sebastian Maurer-Stroh; Paul Anantharajah Tambyah (Singapore Medical Journal, 2024)
All pandemic viruses have eventually adapted to human hosts so that they become more transmissible and less virulent. The XBB Omicron subvariant is rapidly becoming the dominant strain of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in Singapore from October 2022 and is one of several variants circulating globally with the potential to dominate autumn/winter waves in different countries. The XBB Omicron subvariant has demonstrated increased transmissibility through an apparent propensity for immune evasion. This is to be expected in the natural evolution of a virus in a population highly vaccinated with a vaccine targeting the spike protein of the original Wuhan strain of the virus. This review explores the important implications of the rising prevalence of the SARS-CoV-2 Omicron subvariant for public health in Singapore and beyond.